An interface-based microscopic model for the failure analysis of masonry structures reinforced with timber retrofit solutions (Fracture and Structural Integrity, 2024)
This paper presents a refined Finite Element (FE) modeling strategy for analyzing the failure behavior of regular masonry structures reinforced with timber-based retrofit solutions. The proposed model schematizes the masonry as brick units, modeled using two-dimensional linear elastic plane stress elements, mutually joined through zero-thickness cohesive interface elements. These interface elements serve to reproduce the nonlinear behavior of masonry because of the occurrence of failure mechanisms of the mortar joints. Reinforced timber frame elements are modeled using truss elements that exhibit elastic brittle fracture behavior. The interaction between the masonry sub-structure and the reinforced timber frame system is accounted for using special constraint conditions that simulate the mechanical behavior of anchorage connections. The reliability of the proposed model in reproducing the failure behavior of masonry is assessed through comparisons with experimental and numerical data available in the literature. Additionally, the efficacy of the retrofit technique based on timber frame structures is investigated in detail through pushover analyses on a two-story masonry wall representative of real-life masonry buildings. The results indicate that the proposed retrofitting strategy is an effective and eco-friendly retrofit solution to enhance the in-plane bearing capacity of masonry structures subjected to horizontal forces.
Keywords: Masonry; crack propagation analysis; Finite elements; CZM (Cohesive Zone Model); Timber; Retrofit; Sustainable solutions